Vaupés multilingüe: Experiencia del fortalecimiento de capacidades locales para la investigación y promoción de las lenguas nativas (2025)
This book is an invitation to explore the astonishing world of the native languages ​​of Vaupés, through a journey that fuses history, culture, and innovative techniques. Based on an exhaustive study of the region's research and linguistic diversity, this text provides a solid conceptual framework that enhances the understanding of Amazonian multilingualism. Its methodological contributions, such as the use of "border objects" and co-creation processes with Indigenous peoples, which demonstrate genuine intercultural dialogue, are highlighted. Furthermore, the book investigates the capacity of digital technologies for language preservation, critically adjusting them to local circumstances. With a sensitive and participatory approach, it also documents experiences of social appropriation of knowledge and the training of Indigenous teachers, underscoring the importance of strengthening local capacities for the safeguarding and promotion of native languages, in a department like Vaupés, which accounts for a significant number of the total in Colombia. This work not only documents languages ​​but also builds bridges between academic research and Indigenous knowledge, making it essential reading.